An epidemiological cross-sectional study of prevalence of mental disorders in Dulong nationality of Southwest China. Issue 38 (18th September 2020) - Zhi, Jinsheng; Zhang, Yunqiao; You, Xu; Long, Qing; Zhu, Yun; Liu, Jianping; Wu, Jie; Zhang, JinTao; Wang, TingTing; Teng, Zhaowei; Zeng, Yong
Abstract : Abstract: The Dulong nationality is one of the 5 smallest ethnic minorities in China. The suicide rate among people of the Dulong nationality is very serious. To address this issue, we conducted cross-sectional epidemiological studies on the prevalence of mental disorders in ethnic groups. Studying the unique situation of ethnic minorities can help us better understand their mental state and improve their quality of life. We conducted a cross-sectional epidemiological survey on a minority group in Southwest China. We used the cluster sampling method, and 2129 people were included in the study. The highest 1-month disorder prevalence was for alcohol dependence/abuse (4.16%), and the prevalence of lifelong mood disorders was 9.82%. The results of multivariate analysis showed that women faced a higher risk of mood disorders and anxiety disorders. This epidemiological survey of the prevalence of mental disorders in ethnic minorities in Southwest China provides a significant reference for mental health interventions for other ethnic minorities around the world.